2020
DOI: 10.1371/journal.pone.0232932
|View full text |Cite
|
Sign up to set email alerts
|

Trust as a mediator in the relationship between childhood sexual abuse and IL-6 level in adulthood

Abstract: Childhood sexual abuse (CSA) has been shown to predict the coupling of depression and inflammation in adulthood. Trust within intimate relationships, a core element in marital relations, has been shown to predict positive physical and mental health outcomes, but the mediating role of trust in partners in the association between CSA and inflammation in adulthood requires further study. The present study aimed to examine the impact of CSA on inflammatory biomarkers (IL-6 and IL-1β) in adults with depression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Other inflammatory biomarkers incorporated were NKCA [37], sTNF-RII [62], gene expression [36,38], cortisol [34], and latent herpesviruses (EBV and CMV) [33]. Evidence emerged that childhood abuse is associated with elevated IL-6 [32,36] and cortisol [34,63,64]. Examining the relationship between inflammatory markers and RFQ subscales, findings suggested that risky factor total score was associated with IL-6 and marginally associated with CRP.…”
Section: Inflammation Markersmentioning
confidence: 99%
“…Other inflammatory biomarkers incorporated were NKCA [37], sTNF-RII [62], gene expression [36,38], cortisol [34], and latent herpesviruses (EBV and CMV) [33]. Evidence emerged that childhood abuse is associated with elevated IL-6 [32,36] and cortisol [34,63,64]. Examining the relationship between inflammatory markers and RFQ subscales, findings suggested that risky factor total score was associated with IL-6 and marginally associated with CRP.…”
Section: Inflammation Markersmentioning
confidence: 99%
“…Chan et al, 2017;R. T. H. Ho et al, 2012;Ng et al, 2020). More research is being conducted on the immune markers and childhood eczema in Hong Kong in the past 2 years, and more laboratory analysis is underway (Xie et al, 2020).…”
Section: Practitioner-researcher-educatormentioning
confidence: 99%